Intramedullary Fixation of Distal Radius Fractures Using CAGE-DR Implant - Rancy, Schneider K.; Malliaris, Stephanie D.; Bogner, Eric A.; Wolfe, Scott W. (Journal of Wrist Surgery, 2018)
Purpose CAGE-DR implant is a novel Food and Drug Administration approved intramedullary fracture fixation device used for distal radius fractures. We examine a series of 22 patients and report the outcomes with this device.Materials and Methods A total of 24 patients with distal radius fractures (8 articular AO type C1/C2; 16 extra-articular AO type A2/A3) underwent open reduction and internal fixation (ORIF) using CAGE-DR implant by a single surgeon. Data including fracture type, angle of displacement, radiographic consolidation, grip strength, wrist range of motion (ROM), patient-rated wrist evaluation (PRWE), and Visual Analog Scale (VAS) pain scores were recorded at time of surgery and at standard follow-up.Results All 24 patients underwent uneventful ORIF. At first follow-up visit (9 days), all patients had full digital ROM (measured as 0 cm tip-to-palm distance). Two patients were lost to follow-up. Eighteen of the remaining 22 patients had sufficient radiographic follow-up and all 18 demonstrated healing. At latest follow-up (mean 9.7 months, range, 3–20), VAS pain scores averaged 0.6 (range, 0–8) and PRWE averaged 12.1 (range, 0–53.5). Grip strength of the operated hand averaged 58 lbs (range, 20–130). ROM included: wrist flexion 73° (50–95), wrist extension 78° (60–110), pronation 77° (60–90), supination 79° (60–90), ulnar deviation 31° (5–45), and radial deviation 17° (10–30). Three patients underwent screw removal to prevent tendon irritation. One patient underwent hardware removal due to prominence on imaging but was asymptomatic. There were otherwise no major complications, including complex regional pain syndrome, in the series to date.Conclusion The CAGE-DR fracture fixation system is a promising alternative to established methods of distal radius internal fixation. This series has a low reported pain score starting immediately postoperatively and a low complication rate. This novel device is a promising option for internal fixation of displaced distal radius fractures with a low complication profile.Level of Evidence This is a level IV, therapeutic study.
Keywords: Conventus; distal radius fracture; internal fixation; intramedullary fixation; outcomes